Feasibility study of use of rabbit blood to evaluate platelet activation by medical devices. Issue 185 (January 2020) - Ye, Sheng; Wang, Hong; Ni, Panxianzhi; Yuan, Tun; Liang, Jie; Fan, Yujiang; Zhang, Xingdong
Abstract: It is important to ascertain platelet responses to blood-contacting medical devices as part of a complete hemocompatibility evaluation. Nevertheless, researchers often face the problem of insufficient quantities of human blood for evaluation of platelet activation by actual medical devices. If animal blood can replace human blood to evaluate platelet activation by medical devices, testing will be smoother and will aid for quality control of related products. Therefore, in this study, we exposed representative biomaterials to human blood, rabbit blood and mouse blood, and evaluated similarities and differences in platelet activation among the three types of blood by measuring various molecular markers. We found that rabbit blood and human blood had considerable similarity in terms of platelet activation, while mouse blood and human blood showed considerable differences. Therefore, rabbit blood may replace human blood for platelet function testing. Highlights: Rabbit and human blood have substantially similarities in platelet activation. Rabbit blood may replace human blood for platelet function testing in vitro. Animal blood may be the substitute of human blood in evaluation of medical devices.